Pengembangan Media Pembelajaran Interaktif berbasis Website pada Mata Pelajaran Administrasi Infrastruktur Jaringan dengan Model Pengembangan Four-D di SMKN 3 Malang - Nabial Ihlashi; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The research and development aims to develop interactive web-based learning on subject Administrasi Infrastruktur Jaringan and investigate the results of learning before and after using interactive web-based learning. The development model applied adapts the development model four-D model from Thiagarajan, Four-D model consists of four stages, define, design, develop and disseminate. Four-D model was chosen because it was considered good enough in each stage with the sequence of activities. Validation was carried out by media expert with a percentage of 82% and a percentage of 87% from material expert, both assessments were classified as â€œvery feasibleâ€. And assessment of students related to learning media obtained a percentage value of 84.9% classified as â€œvery feasibleâ€. The total value of development testing carried out conducted on 31 SMKN 3 Malang students in the pre-test of 1700 and post-test of 2070. Completeness of learning also increased from the percentage of pre-test completeness by 12% to the percentage of completeness in the post-test by 41%. And from the Wilcoxon test results obtained a significance value of .002, so it can be concluded that by applying the developed media gives an influence on learning outcomes.